2009
DOI: 10.1021/jo900565y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Formation of Diazocinones, Pyridazines, and Pyrazolines from Tetrazines—Oxyanion-Accelerated Pericyclic Cascades?

Abstract: A computational approach is utilized to study the diazocinone- and pyridazine-forming cascade reactions resulting from the reaction of 1,2,4,5-tetrazines with cyclic enolates. Many of the proposed reaction steps can be formulated as oxyanion-accelerated pericyclic processes. In examining these, a unique stepwise version of a formal (4 + 2) cycloaddition/(4 + 2) cycloreversion was discovered. For the key ring-opening step in these cascades, theoretical evidence for two distinct processes is reported. Of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…An important synthetic application of substituted 1,2,4-triazines is their reaction as azadienes in inverse electron demand Diels−Alder reactions to generate substituted pyridines. , Analogously, 1,2,4,5-tetrazines are known to react with electron-rich enes to give substituted pyridazines . However, in previous work from our laboratory, we did not obtain the expected pyridazine derivative 5 by the reaction of tetrazine 3 with cyclobutanone enolate 2 . Rather, instead of intermediate 4 eliminating water to aromatize (→ 5 ), diazocinone 6 was obtained through a ring-expansion reaction (Scheme ). , …”
mentioning
confidence: 83%
See 2 more Smart Citations
“…An important synthetic application of substituted 1,2,4-triazines is their reaction as azadienes in inverse electron demand Diels−Alder reactions to generate substituted pyridines. , Analogously, 1,2,4,5-tetrazines are known to react with electron-rich enes to give substituted pyridazines . However, in previous work from our laboratory, we did not obtain the expected pyridazine derivative 5 by the reaction of tetrazine 3 with cyclobutanone enolate 2 . Rather, instead of intermediate 4 eliminating water to aromatize (→ 5 ), diazocinone 6 was obtained through a ring-expansion reaction (Scheme ). , …”
mentioning
confidence: 83%
“…Alternatively, pyrrolidine may simply function as a base and form small quantities of enolate 2 (protonated pyrrolidine is more acidic than cyclobutanone by ∼10 p K a units), which through reaction with 9 would give 11 (X = O − ). Previously 2 , generated using KOH/methanol, was shown to react in a similar manner with a 1,2,4,5-tetrazene. In fact, employing KOH/methanol, while not effective in preparative reactions, does result in the reaction of cyclobutanone with 9 to give 12 (X = OH) and/or 15 as evidenced by LC/MS of the crude reaction mixture. However, no reaction was observed when DBU was used as base.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is so exothermic that the Bell-Evans-Polanyi principle [32] and the Berson correlation [33] would lead one to ask if it might have no barrier at all. We have measured the rate of the reaction of dimethoxycarbonyltetrazine (22a) with 1-(diethylamino)propyne (23a) using stopped flow kinetics (Scheme 9) [3c].…”
Section: Sequential Transition Structures Corners and Effective Monkmentioning
confidence: 99%
“…The complex cascade shown in Scheme 35 was examined by Tantillo and co-workers using B3LYP calculations. 43 The originally proposed mechanism for this process consisted of path A followed by either path C or path D. Computations suggested, however, that path B is more likely than path A, i.e., instead of a [4+2] cycloaddition followed by a [4+2] cycloreversion, a nucleophilic attack followed by an unusual concerted ring-closure/N 2 extrusion reaction is preferred. It was also concluded that both path C and path D can exist, leading to geometric isomers of the product, although path C is generally preferred.…”
Section: Tandem and Hybrid Reactions Tandem Reactionsmentioning
confidence: 99%